Cryogenic toughness of natural silk and a proposed structure–function relationship - Fu, C; Wang, Y; Guan, J; Chen, X; Vollrath, F; Shao, Z (Royal Society of Chemistry, 2019)
Natural spider and worm silks can provide key insights into bio-polymer technology. No-one would have thought that ductility and toughness at cryogenic temperatures would be among their properties. Here we examine the behavior and function of several animal silks by focusing on the multi-fibrillar fibres of Antheraea pernyi silkworm cooled down to −196 °C. In essence, on the micro- and nanoscale, the extrinsic toughening mechanism of the aligned nanofibrils of silk-protein blunts the crack tip and deviates the fracture path. At the molecular level, an intrinsic toughening mechanism within each nanofibril can be attributed to high degrees of orientation of both ordered and disordered chain-domains. We propose that the highly aligned yet relatively independent nanofibrillar structure allows the partly frozen molecular chain at cryogenic temperature to be activated to induce crack blunting, to allow fibril slipping, and to facilitate the effective unfolding of silk fibroin molecular chains thus preventing or delaying brittle failure of the whole fibre. The spider and mulberry silks examined diplayed comparable functional mechanisms. We envision that our study will lead to the design and fabrication of new families of tough structural composites using natural silk or silk-inspired filaments for testing applications even at arctic or indeed outer-space conditions.